2009
DOI: 10.1007/s12190-009-0351-5
|View full text |Cite
|
Sign up to set email alerts
|

Stochastic analysis of prey-predator model with stage structure for prey

Abstract: The present paper deals with the effect of environmental fluctuation on a prey-predator model with stage structure for prey population. We have studied the stochastic behaviour of the model system around coexisting equilibrium point. Stochastic stability condition in mean square sense is obtained for the stage-structured model with help of a suitable Lyapunov function. Numerical simulations are carried out to substantiate the analytical findings. The main outcomes of mathematical findings are mentioned in conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 12 publications
0
5
0
Order By: Relevance
“…Indeed, in growth phenomena, various authors have introduced stochastic versions of classical deterministic growth models especially in animal or cell populations, birth-death, energy, survival populations, life-testing experiments, and environmental studies. See, for example: Saha and Chakrabarti [5], Nafidi et al [6], Di Crescenzo and Paraggio [7], Gutiérrez et al [8], and Skiadas and Giovanis [9]. Diffusion processes are also examined in the field of electricity; in fact, many studies have been focused on the consumption of electrical energy; diverse works suggested a means of using stochastic diffusion processes to model the total consumption of electrical power and to forecast the consumption of electrical energy in relation to particular economic or climatologic variables, using statistical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, in growth phenomena, various authors have introduced stochastic versions of classical deterministic growth models especially in animal or cell populations, birth-death, energy, survival populations, life-testing experiments, and environmental studies. See, for example: Saha and Chakrabarti [5], Nafidi et al [6], Di Crescenzo and Paraggio [7], Gutiérrez et al [8], and Skiadas and Giovanis [9]. Diffusion processes are also examined in the field of electricity; in fact, many studies have been focused on the consumption of electrical energy; diverse works suggested a means of using stochastic diffusion processes to model the total consumption of electrical power and to forecast the consumption of electrical energy in relation to particular economic or climatologic variables, using statistical techniques.…”
Section: Introductionmentioning
confidence: 99%
“…And the second one is to add randomly fluctuating driving force directly to the deterministic equations without affecting any particular parameter to incorporate the effect of randomly fluctuating environment ( [13,14]). This type of stochastic perturbation technique to study the effect of fluctuating environment was first introduced by Beretta et al [15] on a population model system, and Shaikhet [16] and then other researchers used it [17].…”
Section: Introductionmentioning
confidence: 99%
“…These random factors of the environment are not only an integral part of any realistic ecosystem, but they also may lead to complete extinction of populations. The existing research works have investigated dynamic properties of stochastic predator-prey models [7][8][9][10][11][12], stochastic competitive models [13][14][15][16][17][18], stochastic mutualism models [19][20][21][22][23][24] and stochastic three-species models [25][26][27][28][29][30][31][32][33]. To the best of our knowledge, there are few studies to analyze the dynamics of a stochastic cooperation-competition model.…”
Section: Introductionmentioning
confidence: 99%